The Understanding of Purbosari Village Community Regarding Hadith as the Foundation of Islamic Education - Febi Nina Barokah (PT. Islamic Research Publisher, 2024)
Hadith, as one of the primary sources of Islamic teachings after the Qur'an, plays a significant role in guiding the lives of Muslims. This research delves specifically into the community's perception of the importance of Hadith in Islam, aiming to explore both theoretical and practical implications. Theoretically, this study provides an initial foundation for further exploration of community perceptions regarding Hadith's significance, while practically, it offers insights for advancing studies on this topic. Using a qualitative approach with a descriptive-analytical method, the research collects qualitative data from primary sources, including literature reviews of various perspectives, and secondary sources, such as articles, books, and prior research. The findings reveal that the community's perception of the importance of Hadith is reflected in its implementation within their social environment, emphasizing universal principles without discrimination, equal rights and responsibilities across social groups, and fostering harmonious relationships. By adhering to Hadith teachings in alignment with Islamic principles, the values of community life manifest in the behavior of individuals as servants of Allah and as members of society, promoting virtuous and harmonious living.